2021
DOI: 10.3390/medicina57090869
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Change of Marginal Bone Height with Cone-Beam Computed Tomography Following Surgical Treatment with Guided Tissue Regeneration (Bone Grafting) or Access Flap Alone: A Retrospective Study

Abstract: Background and Objectives: This study aimed to evaluate the change of bone height following treatment of human intrabony defects with guided tissue regeneration (GTR) with bone grafting or access flap alone by cone-beam computed tomography (CBCT) scan. Materials and methods: This study was conducted as a retrospective longitudinal study. In this study, a total of 2281 teeth sites were included: the GTR group had 1210 sites, and the Flap group had 1071 sites. In the GTR group, demineralized freeze-dried bone (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, some authors have reported that the use of a collagen membrane in combination with xenograft provides no additional benefit when applied to large vertical defects [12,39]. Nevertheless, the use of a resorbable membrane provides a better clinical outcome in comparison to open-flap debridement performed alone [12,40,41]. The lack of clinical benefit of using a collagen membrane when used in combination with a bone graft for the vertical augmentation of IBDs could be associated with its low mechanical strength and inability to resist the pressure exerted on the augmentation material from the overlying soft tissue [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have reported that the use of a collagen membrane in combination with xenograft provides no additional benefit when applied to large vertical defects [12,39]. Nevertheless, the use of a resorbable membrane provides a better clinical outcome in comparison to open-flap debridement performed alone [12,40,41]. The lack of clinical benefit of using a collagen membrane when used in combination with a bone graft for the vertical augmentation of IBDs could be associated with its low mechanical strength and inability to resist the pressure exerted on the augmentation material from the overlying soft tissue [13].…”
Section: Discussionmentioning
confidence: 99%
“…A serial number was assigned to each section of the CBCT images to prove the consistency of the measurements. [ 21 ] All pre- and postoperative bone height measurements were performed by the first tester (S.-h.P.). The second tester (S.-H.P.)…”
Section: Methodsmentioning
confidence: 99%
“…Cone–beam computed tomography (CBCT) has been proposed to overcome these limitations. Lee et al evaluated the marginal bone level after GTR and open flap procedures using CBCT [ 21 ]. Previous studies have suggested that CBCT is helpful in evaluating the anatomical structure of teeth and surrounding areas before and after IR procedures [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%